2020
DOI: 10.1186/s12943-020-01219-0
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs towards precision medicine in gastric cancer: early diagnosis, treatment, and drug resistance

Abstract: Gastric cancer is a deadly disease and remains the third leading cause of cancer-related death worldwide. The 5-year overall survival rate of patients with early-stage localized gastric cancer is more than 60%, whereas that of patients with distant metastasis is less than 5%. Surgical resection is the best option for early-stage gastric cancer, while chemotherapy is mainly used in the middle and advanced stages of this disease, despite the frequently reported treatment failure due to chemotherapy resistance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
166
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(174 citation statements)
references
References 197 publications
(217 reference statements)
0
166
0
Order By: Relevance
“…Patients suffering from GC often display heterogeneous clinical outcome, with survival durations ranging from less than 5 months to over 10 years 4 , 11 . The 5-year overall survival rate of patients with early-stage localized GC is more than 60%, whereas that of patients with distant metastasis is less than 5% 30 . When diagnosed at early stages, GC can be effectively treated with endoscopic or surgical resection with or without adjuvant therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Patients suffering from GC often display heterogeneous clinical outcome, with survival durations ranging from less than 5 months to over 10 years 4 , 11 . The 5-year overall survival rate of patients with early-stage localized GC is more than 60%, whereas that of patients with distant metastasis is less than 5% 30 . When diagnosed at early stages, GC can be effectively treated with endoscopic or surgical resection with or without adjuvant therapy.…”
Section: Discussionmentioning
confidence: 95%
“…p53 and Puma) ( Li et al., 2013 ; Qin et al., 2018a ; Wang W. et al., 2018 ; Wang et al., 2020 ; Zhang J. et al., 2020 ). It has also been reported that natural products can enhance the chemosensitivity of cancer cells by suppressing the functions of drug resistance-related proteins ( Feng et al., 2017 ; Dong et al., 2020 ; Yuan et al., 2020 ). Recent studies have identified several natural products with potent inhibitory effects on the β-catenin signaling and shown promising anticancer efficacy in vitro and in vivo , such as baicalin ( Zhou et al., 2017 ), arctigenin ( Lee et al., 2017 ), and rhein ( Liu et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is conceivable that disease-associated lncRNA gene variants will be used in the future to forecast the success of cancer therapy. In fact, several lncRNAs affected by cancer-relevant SNPs or amplifications and deletions, including H19, PVT1,or ANRIL have been implicated in cancer drug resistance, as extensively reviewed elsewhere (Campos-Parra et al, 2018;Liu et al, 2020;Peng et al, 2020;Yuan et al, 2020). To solidify the clinical utility of these lncRNAs as diagnostic and prognostic markers for defined patient groups, larger cohorts and replication studies are desirable.…”
Section: Discussionmentioning
confidence: 99%